THE SIGNIFICANCE OF PEACE AND ORDER PROGRAMS FOR PREVENTION OF CHILD IN CONFLICT WITH THE LAW IN BARANGAY KALIGAYAHAN, QUEZON CITY (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
According to Republic Act No. 9344, also known as the “Juvenile Justice and Welfare Act of 2006”, Section 4(e) defines a "Child in Conflict with the Law (CICL)" as a child who is alleged, accused, or adjudged to have committed an offense under Philippine laws. This research employs a quantitative descriptive research design to systematically gather and analyze data relevant to the study. A purposive sampling technique was used to ensure the inclusion of participants who could provide diverse and relevant insights into the research topic. The respondents were categorized into three groups: 15 Barangay Officials, 15 members of the Barangay Peacekeeping Action Team (BPAT), and 20 youth residents of Barangay Kaligayahan, Novaliches, Quezon City. Among the fifty (50) respondents, 20 individuals (40%) are between the ages of 18 to 25, making this the largest age group. The least represented age group is 26 to 33 years old, with only 1 respondent (2%). In terms of sex, 29 respondents (58%) are male, while 21 respondents (42%) are female. Regarding educational attainment, the majority of respondents (42%) are high school graduates, while the least represented group comprises 2% of respondents with the lowest level of educational attainment recorded. For length of service, 17 respondents (34%) have served for 4 to 6 years, while only 5 respondents (10%) have served for 7 to 10 years. The Effectiveness of the Program received an overall weighted mean of 3.52, interpreted as Strongly Agree.Preparedness scored a mean of 3.36, interpreted as Strongly Agree.Support System scored a mean of 3.40, also interpreted as Strongly Agree.Financial Capability received a mean of 3.30, interpreted as Strongly Agree. Among the problems encountered, the highest-ranked issue was:“Budget limitations may affect the quality of the programs we offer to children in conflict with the law,” cited by 86% of respondents. For measures to enhance program effectiveness, the top recommendation was:“Provide more specialized training for barangay officials, staff, and volunteers,” supported by 84% of respondents. The primary output of this study is the recommendation to provide specialized training programs for barangay officials, staff, and volunteers focused on effective child rehabilitation practices and the prevention of juvenile delinquency. These training initiatives aim to strengthen the capacity of local stakeholders in addressing the needs of children in conflict with the law and promoting long-term community-based interventions.
Keywords: specialized training; barangay officials; juvenile delinquency; child rehabilitation; children in conflict with the law (cicl); community intervention; local government; prevention strategies; capacity-building; youth development